Public Legal Awareness in Land Registration in Muara Dua Sub-District - Yulia Sarah; Mohd. Din; Adwani Adwani (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
Article 19 paragraph (1) of Law No. 5 of 1960 concerning Basic Agrarian Law (UUPA) explains that to ensure legal certainty, the Government conducts land registration throughout the territory of the Republic of Indonesia according to the provisions stipulated in Government Regulation No. 24 of 1997 concerning Land Registration. However, based on data showing that in Muara Dua Sub-district, Lhokseumawe City, there are still 40% of land plots that have not been certified. The problems in this study are how the legal awareness of the community on land registration in Muara Dua District, Lhokseumawe City, how the role of keuchik as a committee in land registration in Muara Dua District, and how the government's efforts to increase public legal awareness in registering land. This research uses empirical legal methods with a field research approach and case studies. The results showed that public legal awareness in land registration in Muara Dua Kota village was quite high. Keuchik has an important role in increasing public awareness of registering land. Efforts that have been made by the government to increase public awareness in land registration are the Ministry of ATR / BPN conducting System Branding through advertisements, such as advertisements aired on TV.